1988
DOI: 10.1071/pp9880299
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Photosynthetic Response to Light and Nutrients of Flindersia brayleyana F. Muell., A Rainforest Tree With Broad Tolerance to Sun and Shade

Abstract: Seed from four species of rainforest trees with widely contrasting sunlight requirements for growth and development were sown within disturbance gaps amidst mature forest on the Herberton Range in North Queensland. Observations on seedling persistence plus comparative growth of young trees of Acacia aulacocarpa, Toona australis, Flindersia brayleyana and Darlingia darlingiana (species ranked according to adaptation from full sun to deep shade) confirmed a broad tolerance of Flindersia to sunlight under all con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
56
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 0 publications
9
56
0
Order By: Relevance
“…Sun leaves are markedly thicker and can have additional palisade layers compared with shade leaves (Nobel & Hartsock, 1981 ;Thompson et al, 1988). In terms of resource use, development of the mesophyll (palisade plus spongy mesophyll) represents foremost the investment in N and in total construction costs.…”
Section: Mesophyll Structure Particularly Total Mass and Nitrogen Inmentioning
confidence: 99%
“…Sun leaves are markedly thicker and can have additional palisade layers compared with shade leaves (Nobel & Hartsock, 1981 ;Thompson et al, 1988). In terms of resource use, development of the mesophyll (palisade plus spongy mesophyll) represents foremost the investment in N and in total construction costs.…”
Section: Mesophyll Structure Particularly Total Mass and Nitrogen Inmentioning
confidence: 99%
“…Furthermore, nutrient addition causes an increase in A max in West African tree seedlings (Riddoch et al 1991). Although the studies by Thompson et al (1988Thompson et al ( , 1992 and Riddoch et al (1991) showed similar results to our data, their low light treatments (25-35 lmol m -2 s -1 PFD) likely had greater light availability than our study plants, whose ambient irradiance during our measurements, as recorded by the external PFD sensor on our infrared gas analyzer, was 6.7 lmol m -2 s -1 ± 0.5 (±1SE). Another difference between the studies by Thompson et al (1988Thompson et al ( , 1992 and Riddoch et al (1991) and the current study is that they added all elements together in nutrient treatments, limiting the potential to determine which elements affected photosynthetic processes.…”
mentioning
confidence: 99%
“…The response of A max to nutrient addition is consistent with other studies investigating fertilization effects on tropical tree seedlings in low light. For example, seedlings of Flindersia brayleyana, an Australian tropical rainforest tree species with broad tolerance to sun and shade, increase A max and PFD sat in response to nutrient addition (Thompson et al 1988). In addition, nutrient addition causes an increase in A max in seedlings of two out of three shadetolerant tree species and one shade-intolerant tree species (Thompson et al 1992).…”
mentioning
confidence: 99%
“…In an experiment with a combined N-P-K nutrient treatment the understory in Sabah, Malaysia, seedlings of Dryobalanops lanceolata and Shorea johorensis increased photosynthetic induction time with nutrient addition, whereas only S. johorensis increased A max with nutrient addition (Bungard et al 2002). In upland rainforest in Queensland, Australia, seedlings of Flindersia brayleyana, an Australian tropical rainforest tree species with broad tolerance to sun and shade, increase A max and the light level at which photosynthesis saturates, in response to a combined macroand micro-nutrient addition treatment (Thompson et al 1988). In a later pot study on four species from Queensland rainforests, nutrient addition caused an increase in A max in seedlings of two out of three shade-tolerant tree species and one shade-intolerant tree species in low (30 lmol m -2 s -1 ) light (Thompson et al 1992).…”
Section: Leaves and Roots: Nutrient Limitation Of Resourceabsorbing Omentioning
confidence: 99%